Production of engineered-biochar under different pyrolysis conditions for phosphorus removal from aqueous solution - Nardis, Bárbara Olinda; Franca, José Romão; Carneiro, Jefferson Santana da Silva; Soares, Jenaina Ribeiro; Guilherme, Luiz Roberto Guimarães; Silva, Carlos Alberto; Melo, Leônidas Carrijo Azevedo (The Science of the total environment, 2022)
Phosphorus (P) recovery from wastewater through biochar is an alternative to build a sustainable circular economy and save non-renewable P reservoirs. The efficiency of cations in removing P from wastewater under different pyrolysis conditions is still lacking. We aimed at studying P adsorption and release from biochar enriched with Al3+ and Mg2+, prepared under air-limited and N2-flow pyrolysis conditions. Biochar samples were produced from pig manure (PMB) and impregnated, separately, with 20% of AlCl3 and MgCl2 solutions on both pyrolysis conditions. The materials were characterized for pH, electrical conductivity (EC), total nutrient content, ash, specific surface area (SSA), pore-volume, FTIR, XRD, and SEM-EDX. Phosphorus adsorption was studied by kinetics and adsorption isotherms, as well as desorption. The biochar impregnated with Mg2+ and produced in the muffle furnace achieved the maximum P adsorption (231 mg g−1), and 100% of the adsorbed P was released in solutions of Mehlich-1 and citric acid 2%. The pyrolysis conditions had a small or no influence on the biochar properties governing P adsorption, such as chemical functional groups, surface area, quantity and size of pores, and formation of synthetic minerals. Therefore, it is possible to produce biochar without using N2 as a carrier gas when it comes to P adsorption studies. Mechanisms of P removal comprise precipitation with cations, surface complexation, ligand exchange reactions, and electrostatic attraction on the biochar surface. Overall, Mg-impregnated biochar is a suitable matrix to remove P from aqueous media and to add value to organic residues while producing an environmentally friendly material for reuse in soils. [Display omitted] •Biochar loaded with Al and Mg increases their P adsorption capacity.•Biochar loaded with Mg showed the best efficiency for P removal.•Biochar production in muffle furnace is preferred for increasing P removal capacity•Precipitation and electrostatic attraction are the main mechanisms of P removal